Sensitive Molecularly Imprinted Fluorescence Determination of Pyrethroids using Green Zinc Oxide Quantum Dots. (3rd May 2017) - Wang, Qingwei; Jiang, Jiaqi; Sui, Wei; Lin, Xue; Liu, Bo
ABSTRACT: Pyrethroids are similar to the natural pyrethrins produced by the flowers of pyrethrums that are effective insecticides but with potential toxicity. Here, a novel core–shell fluorescence probe for pyrethroids was prepared by precipitation polymerization. ZnO quantum dots and cyhalothrin were used as the substrate and template, respectively. Due to the formation of reversible specific recognition sites during copolymerization in the presence of acrylamide and ethyl glycol dimethacrylate, ZnO-based molecularly imprinted polymers containing cyhalothrin recognition sites were obtained. Transmission electron microscopy, infrared spectroscopy, and fluorescence spectroscopy were used to characterize the resulting ZnO-based imprinted polymers. The polymer microspheres were used to sensitively and selectively determine cyhalothrin. In addition, a linear relationship between the concentration of cyhalothrin and the fluorescence intensity was obtained from 0 to 80 µmol L −1 with a correlation coefficient of 0.9964 using the Stern–Volmer equation. The protocol was used for the determination of cyhalothrin in milk demonstrating the suitability of the methodology for practical sample analysis. The selective and sensitive fluorescence recognition, low production cost, and facile synthesis demonstrate attractive properties of ZnO-based molecularly imprinted polymers for specific molecule recognition.